2019
DOI: 10.1021/acs.est.9b03153
|View full text |Cite
|
Sign up to set email alerts
|

Novel Electrochemical Pretreatment for Preferential Removal of Nonylphenol in Industrial Wastewater: Biodegradability Improvement and Toxicity Reduction

Abstract: Preferential pretreatment of nonylphenol (NP) before biological treatment is of great significance due to its horizontal gene transfer effect and endocrine disruption activity. A novel molecular imprinting high-index facet SnO 2 (MI-SnO 2, HIF ) electrode is designed. NP was effectively removed from industrial wastewater at 1.8 V with totally suppressing human estrogen activity. The ratio of 5 day biological oxygen demand to chemical oxygen demand (BOD 5 /COD Cr ) was enhanced to 0.412 from 0.186 after prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Although promising PEC performances have been achieved, the charge transfer mechanisms remain unclear and are still under debate in many cases [28,29]. On the other hand, the mass transfer of reactants and their subsequent adsorption on the electrode surface are also essential factors determining the reaction rate and efficiency [30,31]. However, most current prevailing approaches for PEC oxidative upgrading focus on planar photoelectrodes, which suffer from low efficiency caused by limited reactants diffusion around the semiconductor-liquid interface [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Although promising PEC performances have been achieved, the charge transfer mechanisms remain unclear and are still under debate in many cases [28,29]. On the other hand, the mass transfer of reactants and their subsequent adsorption on the electrode surface are also essential factors determining the reaction rate and efficiency [30,31]. However, most current prevailing approaches for PEC oxidative upgrading focus on planar photoelectrodes, which suffer from low efficiency caused by limited reactants diffusion around the semiconductor-liquid interface [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting study was performed by Niu et al (2020). They designed a novel molecular imprinted high-index facet SnO 2 (MI-SnO 2, HIF ) electrode and applied it for specific removal of nonylphenol from tannery wastewater before the biological treatment.…”
Section: Electrochemical Degradation Of Alkylphenolsmentioning
confidence: 99%
“…The estrogenicity of wastewater was determined by an enzyme-linked immunosorbent assay and had fallen to zero after 5 h of treatment with the chosen electrode. This approach to treat wastewater by preferential electrooxidation before biological treatment has shown undisputable advantages over the more common reverse approach (Niu et al 2020).…”
Section: Electrochemical Degradation Of Alkylphenolsmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) (such as electrochemical oxidation, photocatalytic oxidation, Fenton reaction, UV/H 2 O 2 , O 3 /H 2 O 2 ) were commonly used for detoxification of the refractory toxic organic pollutants because plenty of strong oxidant hydroxyl radicals (•OH) were generated during the processes, which could decompose toxic organics into much less toxic semiproducts or even CO 2 at high rate constants. However, many reports indicated that •OH could not detoxify atrazine efficiently because it often attacked the side chains of atrazine to form chlorinated dealkylation products with high toxicity (Table S2). This shortcoming hindered the application of AOPs to treatment of atrazine manufacturing wastewater.…”
Section: Introductionmentioning
confidence: 99%